PENGARUH PERSEPSI KENDALI ATAS PRILAKU TERHADAP NIAT GENERASI MUDA DALAM BERINVESTASI - ilham, ilham; Arifuddin; Usman, Asri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to examine the effect of attitudes on perceived behavioral control on the intention of the younger generation to invest in stocks using the theory of planned behavior. Data was collected by distributing questionnaires to 60 Bosowa Polytechnic students. The statistical method used to test the hypothesis is multiple linear regression with SPSS program. The results showed that perceived behavioral control variables had a positive effect on stock investment intentions. This explains that the smaller or the least perceived barriers to investing, the stronger a person's intention to invest in stocks. The younger generation was chosen because they have the potential to move the national economy of developing countries such as Indonesia in the future in a better direction. However, in filling out the survey, this young generation may have quite a few obstacles that affect the response. This constraint makes sense because most of the respondents in this study were found to be still dependent on their parents or in a condition to start their career path. Thus, investment cannot be their top priority. However, the author considers that this condition is the most appropriate time to prepare Indonesia's young generation.